056 Outcome of endovascular thrombectomy for ultra-long aeromedical transfers: The experience of one 'hub' and eleven 'spoke' sites covering more than 1.8 million km2. (23rd August 2021) - Pakrah, Seppy; Huang, Karen; Berrill, Haylee; Tan, Meng; Bailey, Peter; Sabet, Arman; Devilliers, Laetitia; Rice, Hal; Shah, Darshan
Abstract : Background: Local endovascular services for acute stroke in rural and remote regions remain a significant challenge despite higher rates of stroke in these regions. Objectives: We present time metrics, logistics, safety and outcome data on stroke patients with large vessel occlusion (LVO) that were aero-medically transferred from rural and remote 'spoke' sites to the Gold Coast University Hospital (GCUH) 'hub' for endovascular thrombectomy (EVT). Methods: This is a retrospective observational study utilizing prospectively collected stroke database from December 2018 to March 2020. Aeromedical transfers from ten rural and remote Queensland sites and one Northern New South Wales site were included, covering more than 1.8 million km² catchment area. Results: Over the period of 16 months, 20 out of 26 transferred patients underwent EVT. Mean distance was 1350 km, median time of ictus to recanalization was 928 minutes and TICI 2b-3 was achieved in 90% of the patients. One out of 20 patients (5%) had symptomatic intracranial hemorrhage (sICH), and 9 out of 20 (45%) achieved functional independence (mRS 0-2) at 90 days; similar to the recent pivotal trials. Conclusions: Our 12-center network experience confirms real world reproducibility of trial results, including ultra-long transfers, and supports such transfers at other centers worldwide.